Refractory Post-Induction Hypotension in Young Hypertension Underwent Humerus Surgery: A Case Report - Muhamad Rafiqi Hehsan; Khairul Idzam Muslim; Mohd Sany Shoib (Universiti Sultan Zainal Abidin (UniSZA), 2024)
Non-Indexed Publication